An investigation into the language preferences of prospective teachers who specialise in English and an African language - Sigudla, Malefeu Maria (University of Limpopo, 2016)
Several studies have investigated the contentious issue of language preference in the education domain, particularly in South Africa. African indigenous languages seemed to be overlooked as well in the country. As one of the scarce skills subjects, the Department of Education (DoE) developed a strategy to curb the decline of African indigenous languages by introducing Funza Lushaka Bursary Scheme. This research study sought to investigate language preferences of student teachers who specialise in English and an African language (Sepedi, TshiVenda and Xitsonga) for future employment among third and fourth year language student teachers. My assumption was that these language teachers have been in the teaching practice, hence their preference might be instigated by their experience in teaching. A purposive sampling using semi-structured interviews was selected for this study. Furthermore, a research journal and a voice recorder were used during the research interviews. The research findings illustrated that majority of participants (70%) preferred to teach African indigenous languages while the remaining percentages preferred to teach English at their future schools. These showed a promising future for the indigenous languages for being promoted and sustained. However, their preference of a particular language over the other was founded on different individual motivation or interest. It was also found that Funza Lushaka Bursary Scheme served as a motivational component for producing student language teachers. These findings provide valuable information for promoting and sustaining African indigenous languages
Thesis (M. Ed. (Language Education)) -- University of Limpopo, 2016
Keywords: Language preference; Education; African indigenous languages; South Africa; English language -- Study and teaching -- African speakers